Narratives of Community in the Black British Short Story - Jansen, Bettina (Springer International Publishing, 2018)
Narratives of Community in the Black British Short Story offers the first systematic study of black British short story writing, tracing its development from the 1950s to the present with a particular focus on contemporary short stories by Hanif Kureishi, Jackie Kay, Suhayl Saadi, Zadie Smith, and Hari Kunzru. By combining a postcolonial framework of analysis with Jean-Luc Nancy's deconstructive philosophy of community, the book charts key tendencies in black British short fiction and explores how black British writers use the short story form to combat deeply entrenched notions of community and experiment with non-essentialist alternatives across differences of ethnicity, culture, religion, and nationality. .